A Pilot study to determine whether visually evoked hemodynamic responses are preserved in children during inhalational anesthesia. Issue 3 (30th December 2014) - Perera, Thushara; Lewis, Philip M.; Davidson, Andrew J.; Junor, Paul; Bottrell, Stephen; Lerman, Jerrold
Summary Background Anesthetic depth is an important parameter to monitor during surgery, yet remains difficult to quantify, particularly in young children where developmental changes influence the electroencephalogram. A more fundamental physiological response to stimulation is the increase in cerebral blood flow secondary to increased metabolic demand, referred to as flow–metabolism coupling (FMC) and measurable using near‐infrared spectroscopy (NIRS). Little is known about the effect of anesthesia on FMC; therefore, we studied visually evoked hemodynamic responses (VEHRs) using NIRS in children undergoing general anesthesia for minor surgical procedures. Method We recruited 23 children (aged 2–5 years), undergoing surgery requiring general anesthesia. VEHRs were measured for 30 min using NIRS, including 5 min of baseline recording after anesthetic induction. Parameters recorded using NIRS included the concentrations of oxygenated (oxy), deoxygenated (deoxy), and total hemoglobin (Hb), which were separated into epochs for evoked response analysis after filtration of motion artifact and baseline drift. Goodness‐of‐fit statistics and classification rules were used to determine the existence of evoked responses, and a modified Gaussian equation was used to model each evoked response. Results Near‐infrared spectroscopy data were recorded in 20/23 children, of whom nine showed a VEHR. No responses were seen in the baseline control data. When examining the relationship between VEHR and anesthetic agents, we noted that for 8/10 patients in whom preoperative or intraoperative fentanyl were administered and VEHRs were absent. Conclusion We have shown that VEHRs can be detected using NIRS in some anesthetized children. Administration of fentanyl was associated with an absence of VEHRs. The mechanism underlying this association is unclear.